‘Salafisme is overal’: Een radicale utopie en de constructie van angst - de Koning, Martijn (Religie & Samenleving, 2012)
Salafism is at the center of public attention because of its alleged ties to recent violent attacks in Europe and because the threat they appear to be for secular and sexual liberties in Europe. In this article I will analyze the paradigm shifts we can find in politics, debates and media with regard to the governance of religion. The central concept in this analysis is Islamophobia which I regard as a structural phenomenon producing and expressing a categorization and hierchisation of groups of people that are subsequently denied access or granted conditional access to the Dutch moral community. I will show how the logic of Islamophobia is based upon cultural differentialism, and anxiety over the future of the Dutch moral community with its ideal of secular and sexual liberties and on securitization. In this logic a distinction is made between liberal and radical Islam and I argue that the Salafists have become the folk devil of the Dutch moral community because they appeal to and evoke abstract feelings of fear related to religion, ethnic diversity and migration. The Islamophobic logic turns them into the concrete examples of how ‘we’ should not be.